Human development and personal development - Straś-Romanowska, Maria (Studia Psychologica: Theoria et praxis, 2002)
The author considers the meanings of such theoretical categories as “human development” and “personal development”. According to philosophical anthropology she shows three main attributes of a person: reflexive consciousness, free will and conscience. The development dealing with all these attributes makes a personal development. But human development contains different spheres as well. They are biological and social ones that belong primarily to naturalistic reality. The feature of personal development is to be permanent through the whole individual life but biological and social development has the natural boundaries.